Optimal allocation of Red List assessments to guide conservation of biodiversity in a rapidly changing world. (28th February 2017) - Hermoso, Virgilio; Januchowski‐Hartley, Stephanie Renee; Linke, Simon; Dudgeon, David; Petry, Paulo; McIntyre, Peter
Abstract: The IUCN Red List is the most extensive source of conservation status assessments for species worldwide, but important gaps in coverage remain. Here, we demonstrate the use of a spatial prioritization approach to efficiently prioritize species assessments to achieve increased and up‐to‐date coverage efficiently. We focus on freshwater fishes, which constitute a significant portion of vertebrate diversity, although comprehensive assessments are available for only 46% of species. We usedmarxan to identify ecoregions for future assessments that maximize the coverage of species while accounting for anthropogenic stress. We identified a set of priority regions that would help assess one‐third (ca 4000 species) of all freshwater fishes in need of assessment by 2020. Such assessments could be achieved without increasing current investment levels. Our approach is suitable for any taxon and can help ensure that species threat assessments are sufficiently complete to guide global conservation efforts in a rapidly changing world. Abstract : We demonstrate the use of a spatial prioritization approach to efficiently prioritize species assessments to achieve increased and up‐to‐date coverage efficiently, using freshwater fishes as they constitute a significant portion of vertebrate diversity not assessed yet. We found that one hundred and nineteen priority regions that encompass one‐third (ca 4000 species) of all freshwater fishes identified to be in need of assessment by 2020. Such assessments could be achieved without increasing current investment levels. Our approach is suitable for any taxon and can help ensure that species threat assessments are sufficiently complete to guide global conservation efforts in a rapidly changing world.